Non-Linear Relation Between External Debt and Economic Growth in Nigeria: Does the Investment Channel Matter? (2021)
Large external debt stock has been identified as one of the most important factors which have restricted the development of many poor countries. The consensus in the literature remains that external debt promotes growth to the extent that a country does not exceed its debt carrying capacity. Otherwise, additional debt accumulation would serve as a tax on future investment returns capable of creating disincentive to invest in the highly indebted countries. In the light of these arguments, this study investigates the possible role of domestic investment in the non-linear relation between external debt and economic growth in Nigeria over the period from 1981 to 2015. Based on the results of threshold regression analysis employed in this study, the overall findings showed that the impact of external debt on economic growth is sensitive to both measures of external debt used, and whether or not the role of domestic investment is accounted for. Specifically, this study confirmed the existence of the debt Laffer curve associated with the debt overhang theory arising from excessive external debt accumulation. Similarly, empirical support was obtained for the crowding-out effect of excessive external debt servicing. Also, accounting for the role of domestic investment in the non-linear relation between external debt and economic growth reduces the optimal debt carrying capacity of the country. It is therefore suggested that the Nigerian government internalizes a maximum ceiling of 6.81% as the share of external debt stock in gross national income (GNI) so as to enjoy the resulting growth benefits. External debt financing sources that are free of interest charge could also be explored so as to circumvent the burden imposed by excessive external debt servicing.